Penguatan Hukum Adat Dan Kelembagaan Adat Dalam Penyelesaian Masalah Hukum Berdasarkan Keadilan Restoratif Ditinjau Dari Perspektif Hukum Dan Hak Asasi Manusia - Emilson, Nur Husni; Azzahra, Bintang Zallika; Beremau, Audy Marshanda (Jurnal Kepastian Hukum dan Keadilan, 2022)
Already in 2014, restorative justice as a distinct approach within the general criminal justice system had been used as the basis to treat child victims and offenders (the child protection Act of 2014).  Nonetheless it is worth noticing that long before the promulgation of this Act, restorative justice has been used and is embedded in the living law of the Indonesian indigenous populations. This paper, using a descriptive analytical method, shall elaborate upon those traditional values found in the living law of the indigenous populations which resembles or reflects a restorative justice approach. The State of Indonesia as an archipelago with thousands of ethnic groups with a variety of different cultural customs in indigenous groups and local wisdom makes the State of Indonesia famous as a country rich in ethnicisity. The existence of indigenous community in various laws and regulations including the Constitution recognizes the existence of indigenous community and even the constitution mandates separate regulations in the form of laws to protect the existence of them and their customary rights